2019
DOI: 10.1596/1813-9450-8766
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrition Sensitivity of Food and Agriculture in South Asia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…Similarly, Tariq et al (2018) found that due to rise in temperature from 1980 to 2016, there are shifts in sowing, emergence, anthesis, and maturity for fall and spring crops. Extreme weather condition and natural disasters negatively impact agricultural yield, food production and food security (Dizon et al, 2019).…”
Section: Climate Changementioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Tariq et al (2018) found that due to rise in temperature from 1980 to 2016, there are shifts in sowing, emergence, anthesis, and maturity for fall and spring crops. Extreme weather condition and natural disasters negatively impact agricultural yield, food production and food security (Dizon et al, 2019).…”
Section: Climate Changementioning
confidence: 99%
“…Climate change has been noted as a new threat to agriculture and food security (Ahmad, Farooq, & Umar, 2016;Gahukar, 2011). In Pakistan, India, Nepal, and China, farmers have noticed an increase in floods, landslides, drought, and disease, due to climate change (Dizon et al, 2019). These events can be attributed to a decline in the production of main crops and an increase in food insecurity (Hussain, Rasul, Mahapatra, & Tuladhar, 2016).…”
Section: Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…Over the past 3 decades, the overall GDP of the region has increased due to agricultural growth and development spurred by the green revolution programme. However, the region has a more significant number of hunger and poor people, around two thirds of these are living in rural areas (Asim (Asim & Nawaz, 2018;Dizon, Josephson, & Raju, 2019;Paciorek, Stevens, Finucane, Ezzati, & Nutrition Impact Model Study, 2013). More than one-quarter of the population in the developing world lives in the South Asia region.…”
Section: Study Areamentioning
confidence: 99%